If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 12 = 5y + -29 Reorder the terms: 12 + 3x = 5y + -29 Reorder the terms: 12 + 3x = -29 + 5y Solving 12 + 3x = -29 + 5y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 3x = -29 + -12 + 5y Combine like terms: 12 + -12 = 0 0 + 3x = -29 + -12 + 5y 3x = -29 + -12 + 5y Combine like terms: -29 + -12 = -41 3x = -41 + 5y Divide each side by '3'. x = -13.66666667 + 1.666666667y Simplifying x = -13.66666667 + 1.666666667y
| 15-ny= | | 3(x+5)-16=15+x | | 3(3z+2)= | | x^2-6x-18=5 | | 23/7=92/x | | 2n-a= | | -5(1+6)=5n+-7 | | 6b-3-7=6b-10 | | 0.09-0.01(x+1)=0.02(2-x) | | 1/6=x/50 | | 2n-q= | | 22/4=55/m | | 5x+5=15x-7-10x | | 5-7X-6X=14-3X | | 2(3)-8= | | 12/w-8=28 | | 9-2[3x+7]=13 | | y^2=x^3-8x | | 5=4-21 | | 5x+5x+x=180 | | 9x+3+3x=30 | | 7+-5x=-5x+-6x+7 | | 7=12n-4 | | -1/5h=11 | | 4x+-5=2x+1 | | -1/18d=-3 | | 8=4/(1-r) | | 12-36-5x=7x | | 1/9g=20 | | 30/1000 | | [x-9]=4 | | 2/x=7/10 |